Assessing Peroxygenase-Mediated Oxidations in the Presence of High Concentrations of Water-Miscible Co-Solvents - Hilberath, Thomas; van Troost, Anouska; Alcalde, Miguel; Hollmann, Frank (Frontiers in Catalysis, 2022)
The use of water miscible organic co-solvents in biocatalysis is a simple procedure for obtaining higher enzymatic activities towards hydrophobic substrates. However, effects on activity and stability have to be carefully evaluated, also with regard to the type and concentration of the respective co-solvent. In this contribution, we investigated and evaluated the effect of some common water-miscible co-solvents on the biocatalytic performance of the recombinant unspecific peroxygenase rAaeUPO from Agrocybe aegerita. rAaeUPO showed promising activities in the presence of high concentrations of the best co-solvent acetonitrile, which enabled to use higher substrate concentrations (≥ 100 mM). Employing high acetonitrile concentrations for the UPO-mediated oxidation of ethylbenzene to (R)-1-phenylethanol was demonstrated under preparative scale conditions and led to product accumulation rates of 31 mM h-1.